A Morphological and Molecular Study of Phallus multicolor in Indonesia - Hermawan, Rudy; Putra, Ivan Permana; Amelya, Mega Putri; Gunawan, Mochammad Rizky Wangsadireja (Makara Journal of Science, 2022)
Phallus is known as stinkhorn mushroom. Previous reports have shown that this genus is recognized by the size and color of the basidioma, which is a highly plastic morphological character that can potentially lead to misidentification. In Indonesia, no study has combined morphological and molecular analyses to identify Phallus. This study aimed to determine the identity of Phallus that has the orange color of an indusium found in Bekasi, West Java, Indonesia. The morphological characteristics were described by observing the macroscopic and microscopic features of fresh specimens. Molecular analyses were performed based on the internal transcribed spacer 4/5 region sequence. The results showed that specimen BO24430 was identified as Phallus multicolor with 100% similarity in the BLAST results and a 98% bootstrap value on the phylogenetic tree. This taxonomic placement was supported by morphological features, such as a campanulate pileus, yellowish to white pseudostipe, brown to whitish eggs, and ellipsoid spores. This study is the only record of P. multicolor in Indonesia with a herbarium voucher since Boedijn in 1932. In addition, the current study assessed the diversity of Phallus in Indonesia using morphological and molecular evidence.